2016
DOI: 10.1007/s12264-016-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Brain Stimulation for the Treatment of Nicotine Addiction: Potential and Challenges

Abstract: Tobacco consumption is one of the leading causes of preventable death worldwide. However, it is difficult to give up smoking by relying on the help of traditional treatments only. Recent years have witnessed emerging positive evidence that non-invasive brain stimulation (NIBS), such as transcranial magnetic stimulation and transcranial direct-current stimulation, can reduce smoking-related behaviors. Although their potential has been implied by advances in research, several methodological issues restrict the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…40 Non-invasively, stimulation of the brain using transcranial magnetic stimulation may also be effective by generating a brief, high-intensity electric shock between two electrodes placed on the scalp. 41,42…”
Section: Discussionmentioning
confidence: 99%
“…40 Non-invasively, stimulation of the brain using transcranial magnetic stimulation may also be effective by generating a brief, high-intensity electric shock between two electrodes placed on the scalp. 41,42…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various ways to modulate the activity of a specific brain area, such as random noise stimulation, ultrasound stimulation, electoral stimulation, and magnetic stimulation, recent research has been focusing on the latter two [76,77]. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are two of the best-studied approaches for treating drug addiction and other mental disorders [76][77][78][79]. Studies have shown that stimulating dorsal lateral PFC by TMS and tDCS were effective to reduce craving, improve cognition, and ameliorate the mood states in subjects using major drugs of abuse [76,80].…”
Section: Brain Stimulationmentioning
confidence: 99%
“…The accepted way to target ES precisely to a specific area within the brain or body is by invasive techniques with inserted or implanted electrodes. Tissue damage, pain, risks of bleeding, infection, and inflammation associated with electrode placement preclude the use of invasive techniques for routine examination of patients, disease diagnostics, and for treatments which do not justify implantation surgery (such as outpatient treatment of drug addiction by brain stimulation 1517 ).…”
Section: Introductionmentioning
confidence: 99%